Ollier disease: multiple enchondromatosis: case report and review of literature - Sashida Mendez, Hirosi; Mendoza Velez, Maria de los Angeles; Hurtado Diaz, Luisa; Rojas Ortiz, Jorge; Araiza Gomez, Edgardo (International Journal of Research in Medical Sciences, 2021)
Multiple enchondromatosis is a rare disease in which cartilage tumors appear at the level of the skeleton. The incidence is unknown due to the very few cases reported in world literature. We presented the case of a patient at the plastic surgery department at General hospital Dr. Ruben Leñero, otherwise healthy, referring first clinical manifestations at childhood with an increase in volume and deformity at the second and third fingers of the left hand.